Optogenetic Control of Neural Circuits in the Mongolian Gerbil - Keplinger, Stefan; Beiderbeck, Barbara; Michalakis, Stylianos; Biel, Martin; Grothe, Benedikt; Kunz, Lars (Frontiers in Cellular Neuroscience, 2018)
The Mongolian Gerbil (Meriones unguiculatus) is widely used as a model organism for the human auditory system. Its hearing range covers most of ours and it uses the same mechanisms for sound localization. The auditory circuits underlying these functions have been characterized. However, important mechanistic details are still under debate. To elucidate missing mechanistic details precise and reversible optogenetic manipulation of neuronal activity in these circuitries is required. However, gene transfer or even genomic modification is scarcely established in the Mongolian gerbil. Here, we have established a reliable, gene delivery system using AAV8(Y337F)-pseudotyped recombinant adeno-associated virus (AAV) 2 based vector in combination with the pan-neural human synapsin (hSyn) promoter driving neuron-specific expression of CatCH (Ca2+-permeable channelrhodopsin) or NpHR3.0 (Natronomonas pharaonis halorhodopsin). After stereotactical injection into the gerbil’s auditory brainstem (medial nucleus of the trapezoid body, dorsal nucleus of the lateral lemniscus) and midbrain (inferior colliculus), we characterized CatCH and/or NpHR3.0 transduced neurons in acute brain slices by means of whole-cell patch-clamp recordings. As electrical properties of optogenetic tools strongly depend on neuronal biophysics, this parameterization is crucial for their in vivo application. In a proof of principle experiment in anaesthetized gerbils we could strongly suppress sound evoked neural responses in the dorsal nucleus of the lateral lemniscus (DNLL) and inferior colliculus (IC) by light activation of NpHR3.0. In summary, by establishing gene delivery and optogenetic tools in the Mongolian gerbil we have paved the way for future studies of the auditory circuitries in this model system.